The influence of cyclosporin A on mechanical retention of dental implants previously integrated to the bone: A study in rabbits - Sakakura, Celso E.; Margonar, Rogerio; Sartori, Rafael; Morais, Juliana A.N.D.; Marcantonio Jr., Elcio (Wiley, 2006)
Background: Immunosuppressive agents may induce severe changes on bone metabolism and may impair the osseointegration process during the implant healing. No data are available concerning the influence of cyclosporin A on dental implants previously integrated to the bone. The aim of this study was to evaluate the influence of cyclosporin A administration on the mechanical retention of bone previously integrated to dental implants. Methods: Eighteen female New Zealand rabbits were submitted to an implant surgery. Each animal received one commercial dental implant of 10 × 3.75 mm. After 12 weeks of an undisturbed healing period, six animals were randomly sacrificed and the removal torque test was performed (group A). In addition, six animals were submitted to a daily injection of cyclosporin A in a dosage of 10 mg/kg (group C), and six animals received saline solution as a control (group B). After 12 weeks of cyclosporin A administration, groups B and C were sacrificed and submitted to a removal torque test in which higher values can be interpreted as higher mechanical bone retention to the implant surface or higher osseointegration. Results: The removal torque results were 30.5 (±9.8) Ncm for group A, 50.17 (±17.5) Ncm for group B, and 26 (±7.8) Ncm for group C. The statistical analysis showed significant differences between groups A and B (P <0.05) and groups B and C (P<0.01). Conclusion: Cyclosporin A administration may impair the mechanical retention of dental implants previously integrated to the bone.
Keywords: Cyclosporin A; Dental implant; Osseointegration; Torque